2021
DOI: 10.31688/abmu.2021.56.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) pandemic and the “paradox” of acute coronary syndrome hospitalizations

Abstract: La pandémie de COVID-19 et le « paradoxe » des hospitalisations à cause du syndrome coronarien aiguL'infection par le virus SARS-CoV-2 dans le syndrome respiratoire aigu sévère, une maladie qui affecte surtout le système respiratoire, est devenue la cause majeure d'une crise à l'échelle mondiale, constituant une réelle provocation pour les systèmes de soins de la santé. Les mécanismes pathologiques caractéristiques de SARS-CoV-2, comme les réponses inflammatoires immunes accrues, l'endommagement endothélial, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous coronavirus outbreaks have been associated with comorbidities and cardiovascular complications 41 . Increased inflammatory and immunological responses, endothelial damage, microvascular dysfunction or thrombosis due to hypercoagulability, and stress cardiomyopathy are possible pathways of the acute coronary syndrome 42 . A recent systematic review and meta-analysis by Cochrane showed that 20.0% (95% CI 16.1-23.8% with substantial heterogeneity -I2 = 94.9%) of patients hospitalized with COVID-19 had an acute myocardial infarction43.…”
Section: Discussionmentioning
confidence: 99%
“…Previous coronavirus outbreaks have been associated with comorbidities and cardiovascular complications 41 . Increased inflammatory and immunological responses, endothelial damage, microvascular dysfunction or thrombosis due to hypercoagulability, and stress cardiomyopathy are possible pathways of the acute coronary syndrome 42 . A recent systematic review and meta-analysis by Cochrane showed that 20.0% (95% CI 16.1-23.8% with substantial heterogeneity -I2 = 94.9%) of patients hospitalized with COVID-19 had an acute myocardial infarction43.…”
Section: Discussionmentioning
confidence: 99%